Thiamine and Pyridoxine Loaded Vanillic Acid Grafted Chitosan Modulates Lactate and Malate Dehydrogenase in Albino Rats - Tejpal, C S; Chatterjee, N S; Elavarasan, K; Lekshmi, R.G K; Anandan, R; Asha, K K; Ganesan, B; Mathew, Suseela (Fishery Technology, 2017)
Feeding trials was conducted to study the response of metabolic enzymes activity such as lactate dehydrogenase (LDH) and malate dehydrogenase (MDH) through dietary supplementation of thiamine and pyridoxine loaded vanillic acid grafted chitosan microparticles (TPVGC) in male and female Wistar strain albino rats for a period of 45 days. Forty-eight animals both male and female were randomly distributed into eight experimental groups and were fed with basal feed along with different levels of TPVGC. At the end of the experiment, the LDH activity in both male and female Wistar strain albino rats were found to be significantly higher (p<0.05) in the control groups and found to decrease with the increase in the inclusion level of dietary TPVGC in the diet. MDH activity was significantly (p<0.05) reduced only in case of female rats. The results obtained in present study shows that dietary supplementation of TPVGC at a level of 0.8% could uphold better metabolic homeostasis of lactate dehydrogenase and malate dehydrogenase.